The contribution of cortical feedback projections to sensory representations in the mouse primary visual cortex - Fioreze, Gabriela Tondolo (2022)
"As visual information travels along the cortical hierarchy, our brain builds representations of the outside world, which ultimately guide behavior. Areas in the cortical hierarchy communicate through reciprocal cortical connections. While the role of feedforward connections in visual processing is reasonably understood, the contributions of feedback connections are less clear. The main source of feedback inputs to the mouse’s primary visual cortex (V1) is a set of higher-order visual areas (HVAs). HVAs modulate the activity of V1 and have been implicated in visual perception and contextual modulations. Nevertheless, the impact of HVAs in V1 has been traditionally studied by inhibiting their activity, rendering these studies unable to distinguish the contributions of direct cortico-cortical feedback and indirect pathways.(...)"